Evaluasi Investment Management (IM) Penerapan Investasi Teknologi Informasi Universitas XYZ Dengan Menggunakan Val IT Framework 2.0 - Rani Puspita Dhaniawaty; Rangga Sidik; Imelda Pangaribuan (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
The implementation of information technology is needed in education field because it can improve the education quality during the learning process. In the implementation of information technology, the university should be able to assess whether the plan of information technology investment is proper and it also must appropriate to the vision, mission, and expectations. The university still has a difficulty for analyzing the best alternative and choosing the information technology investment that could give the benefits for the university and also the leaders still confuse for doing the investment in information technology field with the appropriate cost with the university’s desire. The evaluation of information technology investment is needed to assess whether the technology investment that applied already accordance with vision and mission of the university. One of the frameworks that could help the university to evaluate the information technology investment is Val IT Framework 2.0. The assessment can be done by using the maturity model that can help the university for improving its capability in order to deliver the system consistently which is using by SDM well and also to see how effectively the company making the benefits by benchmarking comparative. There is one domain in Val IT Framework 2.0 which is focused on the investment i.e. Investment Management (IM). Investment Management (IM) has an objective to ensure that program of information technology investment at university can give the optimal result at the appropriate cost and within acceptable risk limit.